2000
DOI: 10.1091/mbc.11.12.4403
|View full text |Cite
|
Sign up to set email alerts
|

The TRAPP Complex Is a Nucleotide Exchanger for Ypt1 and Ypt31/32

Abstract: In yeast, the Ypt1 GTPase is required for ER-to-cis-Golgi and cis-to-medial-Golgi protein transport, while Ypt31/32 are a functional pair of GTPases essential for exit from the trans-Golgi. We have previously identified a Ypt1 guanine nucleotide exchange factor (GEF) activity and characterized it as a large membrane-associated protein complex that localizes to the Golgi and can be extracted from the membrane by salt, but not by detergent. TRAPP is a large protein complex that is required for ER-to-Golgi transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
185
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(196 citation statements)
references
References 42 publications
10
185
0
Order By: Relevance
“…This is noteworthy because AEX-3 is the first exchange factor homologue found to regulate Rab27 in invertebrates or mammals. Also, few exchange factors have been shown to regulate multiple Rabs (Jones et al, 2000). Our findings also suggest that other mechanisms, in addition to exchange factors, specifically control different Rab functions.…”
Section: Discussionsupporting
confidence: 53%
“…This is noteworthy because AEX-3 is the first exchange factor homologue found to regulate Rab27 in invertebrates or mammals. Also, few exchange factors have been shown to regulate multiple Rabs (Jones et al, 2000). Our findings also suggest that other mechanisms, in addition to exchange factors, specifically control different Rab functions.…”
Section: Discussionsupporting
confidence: 53%
“…In a recent study, the Golgiassociated Hrr25 kinase was reported to phosphorylate Sec23/Sec24 and regulate interactions between Sec23 and TRAPPI to control directionality of anterograde transport (Lord et al 2011). Moreover, TRAPPI functions as a GEF for Ypt1 in a manner that is thought to generate activated Ypt1 on the surface of Golgi acceptor membranes and/or COPII vesicles (Jones et al 2000;Wang et al 2000;Lord et al 2011). A subassembly of TRAPPI consisting of Bet3, Bet5, Trs23, and Trs31 binds Ypt1p and catalyzes nucleotide exchange by stabilizing an open form of this GTPase (Cai et al 2008).…”
Section: Vesicle Tetheringmentioning
confidence: 99%
“…When stimulated by exchange factors termed "guanine nucleotide exchange factors" (GEFs), they interact with multiple downstream effectors, which mediate the different steps of vesicular trafficking (1,2). In yeast, Ypt1 is required for endoplasmic reticulum (ER)-toGolgi transport (3)(4)(5), and the TRAPP I complex acts as its GEF (6,7). Rab1, the human functional homolog of Ypt1, also plays a role in ER-to-Golgi transport (8,9).…”
mentioning
confidence: 99%